Solvent Effect on the Amine-Catalyzed Ring-Opening of Azlactone in Acetonitrile-Water Mixtures - A. Al-Jallal, Nada; M. Ismail, Amel (Asian Journal of Chemistry, 2011)
The kinetics of teriethylamine-catalyzed solvolysis of azlactone (oxazolinone) in acetonitrilewater mixtures (10-50 %) in the temperature range (30-60 °C) have been studied. Non-linear plots of log kobs with the reciprocal of relative permittivity were obtained. The thermodynamic parameters DH*, DS* and DG* have been determined; DG* increases gradually as the mole fraction of the cosolvent increase, due to a complex quasi-mirror image compensation of DH* and DS*. The negative values of the entropy of activation and the non-linear relation of log kobs with the reciprocal of relative permittivity suggested selective solvation by the higher polar water molecules. The isokinetic temperature obtained indicated, that the reaction was enthalpic controlled. The presence of methoxy group in the para position retarded the reaction by about three times of hydriogen. The rate was also decreased with increasing the organic cosolvent. The reactivity was analyzed using Kamlet-Taft solvatochromic parameters and were applied successfully in mixed aqueous -acetonitrile mixtures.